Comparison of the post-fire dynamics of the ectomycorrhizal community in two Quercus ilex stands in Northern Spain - CLAVERÍA, V.; DE MIGUEL, A. M.; DE ROMÁN, M. (Publ. Bio. Univ. Navarra, Ser. Bot., 2003)
A comparative study of the post-fire recolonization of ectomycorrhizae in two evergreen oak stands (Quercus ilex L. subsp. ballota (Desf.) Samp.) in Nazar and San Cristóbal (Navarra, Spain) has been carried out. In 1993 a stand in Nazar burnt, but it was not until 1998 that the study started. On the contrary, the study in San Cristóbal started immediately after the stand had caught fire in 2000. Therefore we have been able to compare the regeneration in both stands and the species composition five years after the fire and immediately after the fire, as well as the differences in ectomycorrhizal colonization and abundance of morphotypes between the burnt plots and areas which remained undisturbed in both forests, thus acting as control plots. In both sites the percentage of ectomycorrhizal colonization tended to be lower after the wildfire. In San Cristóbal, in the burnt site there was a lower abundance of morphotypes compared to the control site. However, in Nazar, five years after the fire, we did not find any significant change in species richness, but rather a shift in the abundance of each morphotype when comparing the burnt and the control plots. There are some species of mycorrhizal fungi which seem to be particularly adapted to fire, such as Type 1 in San Cristóbal and Cenococcum geophilum in Nazar. Sphaerosporella brunnea, a pioneer species considered to be especially suitable for the colonization of burnt substrates, was only found in Nazar.
Keywords: Ectomycorrhizae; fire; Quercus ilex; succession